Persepsi Wisatawan Terhadap Kualitas Pelayanan Makanan dan Minuman Pada Homestay. Kasus di Desa Undisan, Bangli - Ni Kadek Eni Juniari (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2021)
The food and beverage facilities served at the homestay in Undisan Village are still very simple in terms of processing, presentation and service. Therefore, it is necessary to know the perception of tourists on the quality of service, especially the food and beverages served. The purpose of this study was to determine tourists' perceptions of the quality of food and beverage service at the homestay in Undisan Village, Bangli. The respondents were tourists who stayed at the homestay in Undisan Village. The sampling technique used in this study is non-probability sampling with purposive sampling method, because the population is unknown. The number of sample was 75 people. The collected data were analysed with descriptive qualitative and quantitative. The results showed that the perception of tourists on the quality of food and beverage services at the homestay in Undisan Village was very good, namely 4.31. Of the 5 dimensions of service, the dimension that received the highest score was reliability, namely 4.40 which was categorized as very good. Meanwhile, the dimension of physical evidence gets the lowest score, namely 4.18 which is in good category. While the dimensions of responsiveness, assurance and empathy got the same score, namely 4.32 which is in the very good category.